Functions of Armigeres subalbatus C-type lectins in innate immunity - Shi, Xiu-Zhen (2014)
C-type lectins (CTLs) are a superfamily of calcium-dependent carbohydrate binding proteins containing at least one carbohydrate-recognition domain (CRD) and they are present in almost all metazoans. Insect CTLs may function as pattern-recognition receptors and play important roles in innate immunity. In this study, we selected five AsCTLs from the mosquito Armigeres subalbatus, a natural vector of filarial nematodes, and performed both in vitro and in vivo studies to elucidate their functions in innate immunity. AsCTLMA15, AsCTLGA5 and AsCTL15 were mainly expressed in hemocytes, AsCTL16 was expressed in fat body, while AsCTLMA11 was expressed in both hemocytes and fat body, and only AsCTLMA11 and AsCTL16 were expressed at high levels in adult females. In vitro binding assays showed that all five recombinant AsCTLs could bind to different microbial cell wall components, including lipopolysaccharide (LPS), lipid A, peptidoglycan (PG), lipoteichoic acid (LTA), zymosan and laminarin (beta-1,3-glucan). Recombinant AsCTLs also bound to several Gram-negative and Gram-positive bacteria, and could agglutinate bacterial cells. Injection of double-stranded RNAs (dsRNAs) could significantly reduce expression of the five AsCTL mRNAs, and the survival of mosquitoes treated with dsRNA to AsCTLGA5 was significantly decreased after Escherichia coli infection, but did not change significantly after Micrococcus luteus infection compared to the control groups, suggesting that Ar. subalbatus AsCTLGA5 may participate in innate immunity against E. coli.